2020
DOI: 10.1186/s13018-020-02139-x
|View full text |Cite
|
Sign up to set email alerts
|

As an unusual traumatic presentation, acetabular fracture and concomitant ipsilateral intertrochanteric femur fracture: a retrospective case series of 18 patients

Abstract: Background Acetabular fracture and concomitant ipsilateral intertrochanteric femur fracture has been suggested as an unusual traumatic presentation and rarely reported in the literature. The aims of this study were (1) to identify the etiological characteristics, (2) to summarize the treatment strategy, and (3) to present the mid- to long-term results of patients with this rare traumatic presentation. Methods In this retrospective study, 18 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This helps in better application of the reduction force to the ischial margin and thereby achieve the best reduction effect in the treatment of quadrilateral plate fracture rotation displacement. The results of this study also showed that the operation time, incision length, blood loss, and hip function score of the pararectus approach group were significantly better than those of the modified Stoppa approach, which further confirmed the important application value of this approach in the surgical treatment of complex pelvic acetabular fractures [ 14 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 63%
“…This helps in better application of the reduction force to the ischial margin and thereby achieve the best reduction effect in the treatment of quadrilateral plate fracture rotation displacement. The results of this study also showed that the operation time, incision length, blood loss, and hip function score of the pararectus approach group were significantly better than those of the modified Stoppa approach, which further confirmed the important application value of this approach in the surgical treatment of complex pelvic acetabular fractures [ 14 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have reported that males were more likely to be affected with acetabular fractures. 5,16,27,28 In this study, mostly males (60%) were found to be affected with acetabular fracture which may be attributed to outdoor activity. A number of studies have shown that road traffic accident is a major mechanism of acetabular fracture.…”
Section: Discussionmentioning
confidence: 65%
“…Similar observations have again been corroborated in previous literature. 9 , 12 Whenever surgical management of P/A fractures was deemed necessary, the femur was often fixed first, an order observed in most other case series as well. The beneficial effects of earlier fixation of femoral fractures are thought to stem from the increased physiological and mechanical stability; earlier stabilisation of the femur facilitates enables a stable platform for better positioning, exposure and reduction of P/A fractures, reduces the occurrence of significant bleeding, lowers fat emboli risks, and may also help patients achieve earlier mobilisation.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 8 , 9 A growing number of studies have described their encounters with this rare injury. 5 , 10 – 13 However, many studies to date have either only reported case-series of limited numbers, or have offered no form of controlled comparison to similar P/A injuries without femoral involvement.…”
Section: Introductionmentioning
confidence: 99%